2015
DOI: 10.1111/hepr.12574
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol ester storage disease with a novel LIPA mutation (L264P) that presented massive hepatomegaly: A case report

Abstract: Cholesterol ester storage disease (CESD) is an autosomal recessive disorder caused by deficient lysosomal acid lipase (LAL) activity, resulting in cholesteryl ester (CE) accumulation. CESD patients have liver disease associated with mixed dyslipidemia leading to liver failure. We here report the case of an 11-year-old male CESD patient with a novel mutation who had the chief complaint of massive hepatomegaly. The patient's liver reached to his pelvis, and his spleen was 2 cm below the costal margin. The patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 24 publications
0
10
0
1
Order By: Relevance
“…Due to the difference in the chemical structure of these substrates, it is possible that some variants may retain substrate specificity against the 4‐MU oleate substrate yet lose the ability to cleave natural substrates or vice versa. In this regard, it is interesting to note that there were three LAL variants mentioned above (c.607G>C/p.Val203Leu, c.791T>C/p.Leu264Pro, and c.811A>C/p.Asn271His), which have been reported to be pathogenic (Kojima et al, ; Kuranobu et al, ; Reiner et al, ), that showed relatively high levels of intracellular lipase activity in our assay. This could be due to any of the reasons discussed, or through a yet to be defined mechanism.…”
Section: Discussionmentioning
confidence: 49%
See 3 more Smart Citations
“…Due to the difference in the chemical structure of these substrates, it is possible that some variants may retain substrate specificity against the 4‐MU oleate substrate yet lose the ability to cleave natural substrates or vice versa. In this regard, it is interesting to note that there were three LAL variants mentioned above (c.607G>C/p.Val203Leu, c.791T>C/p.Leu264Pro, and c.811A>C/p.Asn271His), which have been reported to be pathogenic (Kojima et al, ; Kuranobu et al, ; Reiner et al, ), that showed relatively high levels of intracellular lipase activity in our assay. This could be due to any of the reasons discussed, or through a yet to be defined mechanism.…”
Section: Discussionmentioning
confidence: 49%
“…c.607G > C/p.Val203Leu and c.791T > C/p.Leu264Pro. These two novel variants appeared in compound heterozygous form in a patient reported in Kuranobu et al ()…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…The most common LIPA gene mutation in Caucasians is an exon 8 splice-junction mutation (E8SJM -1G>A ), which results in altered mRNA splicing and exon 8 skipping [ 3 ]. However, the LIPA gene mutations reported in Japanese patients include Tyr22X, Val203 Leu and Leu264Pro [ 8 9 ]. Additionally, sequencing of the LIPA gene in this Korean patient revealed a novel homozygous mutation in exon 5 (p.Thr177Ile).…”
Section: Discussionmentioning
confidence: 99%